2017
DOI: 10.1111/cen.13521
|View full text |Cite
|
Sign up to set email alerts
|

Translational evidence of prothrombotic and inflammatory endothelial damage in Cushing syndrome after remission

Abstract: The sera of premenopausal women with CS in remission, without atherothrombotic disease, contain circulatory endothelial deleterious factors with a direct thrombogenic and pro-inflammatory endothelial effect that could increase cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…9,10 It is worth noting that the cardiometabolic syndrome still progresses in some patients despite achieving long-term remission after medical treatment. 11 Currently, there is no ideal treatment strategy for preventing tissue-specific consequences of hypercortisolism.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 It is worth noting that the cardiometabolic syndrome still progresses in some patients despite achieving long-term remission after medical treatment. 11 Currently, there is no ideal treatment strategy for preventing tissue-specific consequences of hypercortisolism.…”
Section: Introductionmentioning
confidence: 99%
“…Although endogenous CS is a rare disease (Feelders et al 2015), an estimated 1-2% of the global adult population receives long-term treatment with GCs for a broad spectrum of inflammatory and autoimmune diseases (van Staa 2000, Overman et al 2013 with similar cardiometabolic side effects. Despite significant improvements in CS phenotype after medical treatment, cardiometabolic risk remains increased in these patients, even after long-term remission (Colao et al 1999, Pivonello et al 2005, Aranda et al 2018. Specifically, several studies in humans have reported persistent abdominal fat accumulation, insulin resistance and systemic low-grade inflammation (Barahona et al 2009, Geer et al 2012, Wagenmakers et al 2015, Shah et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous reports on the elevation of vWF in patients with CS as compared with control subjects ( 4 , 7 , 46 50 ), comparison of vWF in active phase and after treatment ( 38 , 48 , 51 ), and the association between vWF promoter polymorphism with vWF level ( 35 , 36 , 52 ). The recent meta-analysis demonstrated no linear relationship between vWF level and number of thrombotic events ( 2 ); however, the logistic regression was not corrected for the blood type.…”
Section: Resultsmentioning
confidence: 99%